Eropa Sebagai Pusat Peradaban: Kajian Tentang Pengaruhnya Terhadap Kebijakan Luar Negeri - Yohana Manalu (Jurnal Ilmu Hubungan Internasional LINO, 2025)
Europe has played a very important role in shaping global civilization, through its contributions in the fields of science, culture, economics, and even politics since ancient times. The foundations of philosophy, governance, and legal systems established by Ancient Greek and Roman civilizations became global benchmarks. Although Europe experienced a decline during the Middle Ages, the Renaissance in the 14th century marked a resurgence of rapid advancements in science, art, and humanism, spearheaded by figures such as Copernicus, Galileo, and Leonardo Da Vinci. The Industrial Revolution of the 18th and 19th centuries transformed production and economic systems, spreading worldwide through colonialism and trade. Politically, the British parliamentary system and European legal principles became global models, while Europe’s cultural influence is evident in art, literature, and architecture. Although colonialism has ended, the European Union remains a key actor in international policy. This study aims to analyze the impact of Europe in shaping modern civilization, both through positive contributions such as the advancement of science and legal systems, as well as negative impacts such as colonial exploitation.